2006
DOI: 10.1089/end.2006.20.135
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shockwave Therapy for Peyronie's Disease: Who Benefits?

Abstract: The response to EWST is not the same for all men with Peyronie's disease. Younger men and those with milder curvature have the best outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Subgroup analysis from some of the previous case series [18] showed that the best outcomes after SWT were in relatively younger men (<55 years) with milder penile curvatures (<30°). A degree of success in improving pain and penile curvature has also been reported for the combination of SWT with peri‐lesional injection of a calcio‐antagonist [19,20] or high‐dose oral vitamin E [21].…”
Section: Discussionmentioning
confidence: 95%
“…Subgroup analysis from some of the previous case series [18] showed that the best outcomes after SWT were in relatively younger men (<55 years) with milder penile curvatures (<30°). A degree of success in improving pain and penile curvature has also been reported for the combination of SWT with peri‐lesional injection of a calcio‐antagonist [19,20] or high‐dose oral vitamin E [21].…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to the published literature supporting the role of LiESWT in men with ED ( 17 , 18 ), the reported changes in erectile function following LiESWT for the treatment of PD has been mixed. While International Index of Erectile Function-5 (IIEF-5) score is frequently used to evaluate sexual function in men with PD, it has never been specifically validated for use in this disease state.…”
Section: Sexual (Erectile) Functionmentioning
confidence: 78%
“…It is also more likely that men who reported improvement in penile curvature had a PD history of less than 12 months, indicating likely active disease process, which is more susceptible to a mechanical effect. Furthermore, subgroup analysis of patients in the LiESWT group showed an overall better outcome in younger patients with a relatively milder degree of curvature ( 15 , 17 ). Comparative studies between LiESWT with other treatment modality showed that LiESWT is not superior to other options ( 1 , 11 , 12 ) and when used in combination with other therapeutic options such as intralesional injection or tadalafil for men with PD and ED, there were improvements in erectile function score and quality of life score while the plaque size and curvature were unchanged ( 24 ).…”
Section: Controversy and Unresolved Issuesmentioning
confidence: 95%
“…While published literature has largely failed to demonstrate significant benefit in the use of LiESWT to treat penile curvature [ 1 5 7 8 9 14 15 16 17 18 19 20 ] ( Table 3 ), these outcomes should be interpreted with some caution due to underlying methodological flaws [ 7 8 9 14 15 16 17 18 19 ] and perhaps inappropriate use of shock wave energy flow density [ 7 15 16 17 18 ]. Interestingly, subgroup analysis of patients in the LiESWT group showed an overall better outcome in younger patients with a relatively milder degree of curvature [ 8 18 ]. Comparative studies between LiESWT with other treatment modality showed that LiESWT is not superior to other options [ 1 5 10 ] and when used in combination with other therapeutic options such as intralesional injection or tadalafil for men with PD and ED, there were improvement in erectile function score and quality of life score while the plaque size and curvature were unchanged [ 19 20 ].…”
Section: Discussionmentioning
confidence: 99%